KAJIAN PENERAPAN PRINSIP-PRINSIP AKUSTIK STUDI KASUS: RUANG AUDITORIUM MULTIFUNGSI GEDUNG P1 DAN P2 UNIVERSITAS KRISTEN PETRA - Sutanto, Andy; Priatman, Jimmy; Mediastika, Christina E. (JURNAL DIMENSI UTAMA TEKNIK SIPIL, 2014)
ABSTRACT: Besides visual aspect, room acoustic performance is also an important factor in determining multipurpose hall performance. Room acoustic performance can be achieved if some room acoustic objective parameters are taken into account, such as background noise level, reverberation time, and sound coverage. In order to meet these parameters, it can be done by using materials with appropriate coefficient absorbstion on floor, wall, ceiling and room geometry. Room acoustic objective parameters should be considered in design phase for optimum benefit. Room acoustic simulation on the design of multipurpose hall P1 and P2 Petra Christian University will be done by computer simulation.Â